2009
DOI: 10.1123/tsp.23.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Musically-Induced Emotions on Choice Reaction Time Performance

Abstract: The main objective of the current study was to examine the impact of musically-induced emotions on athletes' subsequent choice reaction time (CRT) performance. A random sample of 54 tennis players listened to researcher-selected music whose tempo and intensity were modified to yield six different music excerpts (three tempi x two intensities) before completing a CRT task. Affective responses, heart rate (HR), and RTs for each condition were contrasted with white noise and silence conditions. As predicted, fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
2
30
1
2
Order By: Relevance
“…Participants moved faster on a treadmill exercise when high tempo music was played (Edworthy & Waring, 2006), and Bishop et al (2009) found that listening to high tempo music reduced reaction times in a choice reaction task. Tempo is also a strong determinant of the affective response to music (Bishop et al, 2009). In that, high tempo music is more frequently highly appreciated than low tempo music.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants moved faster on a treadmill exercise when high tempo music was played (Edworthy & Waring, 2006), and Bishop et al (2009) found that listening to high tempo music reduced reaction times in a choice reaction task. Tempo is also a strong determinant of the affective response to music (Bishop et al, 2009). In that, high tempo music is more frequently highly appreciated than low tempo music.…”
Section: Introductionmentioning
confidence: 99%
“…From sports psychology we know that high volume music appears to increase arousal (Bishop et al, 2007(Bishop et al, , 2009. In cycling this could lead to the idea that one cycles faster when listening to loud music.…”
Section: Introductionmentioning
confidence: 99%
“…4 Tempo, which is measured in beats per minute (bpm), is the musical quality that is easiest to 5 manipulate (other than intensity/volume). It is a major determinant of one's psychophysical and 6 aesthetic response to a piece of music (e.g., Bishop, Karageorghis, & Kinrade, 2009;Edworthy & 7 Waring, 2006). 8 Preference for different music tempi should be affected by the physiological arousal of the 9 listener and the context in which the music is heard; when the individual's arousal is high, faster 10 tempi are preferred (Berlyne, 1971;North & Hargreaves, 2008, pp.…”
mentioning
confidence: 99%
“…En la revisión de literatura no se encontraron estudios que combinen las variables que aquí se trabajaron (Bishop, Karageorghis & Kinrade, 2009;Szabo, Balogh, Gáspár, Váczi & Bosze, 2009), como el caso de la FC, el EP y el TVR.…”
Section: Discussionunclassified
“…Encontraron diferencias significativas entre mediciones (min 10 y 20), mas no encontraron diferencias entre las intensidades (M70, M85 y NM) ni hubo interacción significativa entre mediciones e intensidad. En otros estudios tampoco se han encontrado diferencias significativas entre la frecuencia cardíaca según la intensidad de la música (Bishop, Karageorghis & Kinrade, 2009;Schie, Steward, Becker & Rogers, 2008).…”
Section: Discussionunclassified